Evidence of functional divergence in MSP7 paralogous proteins : a molecular-evolutionary and phylogenetic analysis (2016)
Background: The merozoite surface protein 7 (MSP7) is a Plasmodium protein which is involved in parasite invasion; the gene encoding it belongs to a multigene family. It has been proposed that MSP7 paralogues seem to be functionally redundant; however, recent experiments have suggested that they could have different roles. Results: The msp7 multigene family has been described in newly available Plasmodium genomes; phylogenetic relationships were established in 12 species by using different molecular evolutionary approaches for assessing functional divergence amongst MSP7 members. Gene expansion and contraction rule msp7 family evolution; however, some members could have had concerted evolution. Molecular evolutionary analysis showed that relaxed and/or intensified selection modulated Plasmodium msp7 paralogous evolution. Furthermore, episodic diversifying selection and changes in evolutionary rates suggested that some paralogous proteins have diverged functionally. Conclusions: Even though msp7 has mainly evolved in line with a birth-and-death evolutionary model, gene conversion has taken place between some paralogous genes allowing them to maintain their functional redundancy. On the other hand, the evolutionary rate of some MSP7 paralogs has become altered, as well as undergoing relaxed or intensified (positive) selection, suggesting functional divergence. This could mean that some MSP7s can form different parasite protein complexes and/or recognise different host receptors during parasite invasion. These results highlight the importance of this gene family in the Plasmodium genus. © 2016 The Author(s).